Mapping the field: A bibliometric analysis for distance education with a focus on management studies - Castro. C.; Carvalho, L.; Moreira, S. (Journal of E-Learning and Knowledge Society, 2023)
The pandemic context has presented new challenges for education. In a short time, higher education institutions (HEIs) adapted their students, staff, technology, and infrastructures for a fast migration to distance learning. This change brought new challenges but also new opportunities that justify more contributions. The purpose of this paper is to study distance education (DE) methods and approaches, with a focus on management studies that are understudied. The research adopted a descriptive quantitative approach. Based on a sample of 400 documents using the Scopus database, a bibliometric analysis was carried out, aiming to identify the most prominent keywords, authors, sources, and countries for DE in general, with a focus on management courses in HEIs. The results suggest that innovation can be an asset for HEIs and can be seen as an ally for both teachers and students in learning new practices that involve digitalization. The bibliometric analysis highlights that motivation and collaboration are very important aspects and should be considered, especially when students are at the center of the teaching process. The main limitation regards the dominance of papers about DE, mostly based on the education sciences, and just a small number focusing on management courses. This limitation can influence the results achieved, but also allows this research to contribute for a better understanding of this field. This is one of few studies that has innovated by identifying the main subjects in DE literature, with a special emphasis on management courses, thus complementing previous scarce research in the field.